Dosimetry for boron neutron capture therapy developed and verified at the accelerator based neutron source VITA - Bikchurina, Marina; Bykov, Timofey; Ibrahim, Ibrahim; Kasatova, Anna; Kasatov, Dmitrii; Kolesnikov, Iaroslav; Konovalova, Victoria; Kormushakov, Timur; Koshkarev, Alexey; Kuznetsov, Anton; Porosev, Vyacheslav; Savinov, Sergey; et al. (Frontiers in Nuclear Engineering, 2023)
The method of boron neutron capture therapy for malignant tumors, proposed in 1936, is beginning to enter clinical practice. The development of dosimetry tools for characterization of therapeutic mixed neutron-photon beam and assessing the patient's response to treatment is becoming relevant. In this work, a number of dosimetric techniques have been developed: a compact neutron detector with a pair of cast scintillators, one of which is enriched with boron, to measure the boron dose and the ray dose; cell dosimeter for measuring the sum of the equivalent dose of fast neutrons and the equivalent nitrogen dose; prompt -ray spectroscopy for in situ measurement of boron dose in real time; epithermal neutron flux monitor for measuring the epithermal neutron flux. Their verification carried out on the accelerator based neutron source VITA showed that they can become convenient and reliable tools for characterization of neutron beam and assessing the patient's response to treatment.